2012
DOI: 10.1111/j.1095-8649.2011.03207.x
|View full text |Cite
|
Sign up to set email alerts
|

Basics of skin structure and function in elasmobranchs: a review

Abstract: In contrast to the bony fishes, particularly the teleosts, the integument of elasmobranchs is rather unknown. Therefore, a description of the basic structural and functional features of shark and ray skin is given, based on a review of the literature and published or unpublished findings of the authors. The latter aspect makes it possible to document in more detail the specific structure of the skin layers regarding, particularly, the epidermis and its cell spectrum, the more or less robust dermis with its spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 71 publications
1
103
0
Order By: Relevance
“…In most sharks, placoid scales cover the entire body, whereas among rays only sawfish (Pristiformes) and guitarfish (Rajiformes: Rhinobatidae) show a similar body coverage: some members of the Myliobatiformes (including whiptail stingrays and eagle rays) have very few scales or none at all (Meyer and Seegers 2012). Visser (2005) found that over 90% by number of the elasmobranchs preyed upon by New Zealand killer whales were sting or eagle rays, so although sharks were also taken, their incidence was perhaps not high enough to produce significant tooth wear.…”
Section: Discussionmentioning
confidence: 99%
“…In most sharks, placoid scales cover the entire body, whereas among rays only sawfish (Pristiformes) and guitarfish (Rajiformes: Rhinobatidae) show a similar body coverage: some members of the Myliobatiformes (including whiptail stingrays and eagle rays) have very few scales or none at all (Meyer and Seegers 2012). Visser (2005) found that over 90% by number of the elasmobranchs preyed upon by New Zealand killer whales were sting or eagle rays, so although sharks were also taken, their incidence was perhaps not high enough to produce significant tooth wear.…”
Section: Discussionmentioning
confidence: 99%
“…Liem et al, 2001). These denticles are composed of an outer enameloid layer and an inner bone-like layer surrounding a pulp cavity, and the denticles are sculpted into complex three-dimensional (3D) shapes (Kemp, 1999;Meyer and Seegers, 2012;Motta et al, 2012;Oeffner and Lauder, 2012). Denticles erupt through the epidermis and thus are in direct contact with the water.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that analyzing flexible shark skin models during swimming is an important prerequisite to understanding how skin functions during in vivo locomotion (Oeffner and Lauder, 2012). And as shark skin is composed of numerous hard denticles embedded within a flexible dermis (Kemp, 1999;Meyer and Seegers, 2012), from a biomimetic perspective synthetic shark skin should contain both rigid and flexible components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This consumption would result in more consistent isotope values between tissues even with different turnover rates, but small sample sizes over ontogeny limit the conclusions that can be made. Shark placoid scales or dermal denticles form in the dermis and increase in size with increasing body surface or body growth during the lifetime of an animal (reviewed by Meyer & Seegers 2012). The growth of these placoid scales is continuous, with substitution taking place as scales shed, resulting in different growth stages of scales occurring between fully grown dermal denticles (Meyer & Seegers 2012).…”
mentioning
confidence: 99%